2014
DOI: 10.3109/19396368.2014.960624
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and phenotype frequencies of paraoxonase 1 in fertile and infertile men

Abstract: Paraoxonase1 (PON1) is a glycoprotein associated with high density lipoprotein and has antioxidant activity. The impact of PON1 in various stages of spermatogenesis has also been suggested. This study was aimed to investigate frequencies of phenotypes and Q192R genotypes of PON1 in fertile and infertile males. Q192R variants of PON1 were determined in 150 fertile and 150 infertile men using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique. Plasma arylesterase and para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In the Iranian study (Tavilani et al, ), infertile males had higher AB phenotypes than fertile males. In our study including infertile men with isolated teratozoospermia in Turkish subjects, we found an elevation of the AA phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…In the Iranian study (Tavilani et al, ), infertile males had higher AB phenotypes than fertile males. In our study including infertile men with isolated teratozoospermia in Turkish subjects, we found an elevation of the AA phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…The PON1 is involved in male reproductive functions, as it was identified in sperm lineage cells, Sertoli cells and Leydig cells of rats and humans (Marsillach et al, 2008(Marsillach et al, , 2011. Low activity of PON1 was observed in the seminal plasma of infertile or subfertile men (Lazaros et al, 2011;Tavilani et al, 2014;Verit, Verit, Ciftci, Erel, & Çelik, 2009) and in ejaculates of azoospermic men (Gulum et al, 2016). In boars, activity of PON1 was determined in the seminal plasma , and its antioxidant activity was related to subsequent fertility in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme hydrolyzes the toxic oxon metabolites of organophosphorus insecticides, nerve agents, such as sarin and soman, aromatic esters, as well as a variety of aromatic and aliphatic lactones including homocysteine thiolactone (Yilmaz, ). There is some preliminary evidence to suggest that paraoxonase activity is involved in the etiology of male infertility (Tavilani et al ., ); low levels of enzyme activity being associated with an infertility phenotype and evidence of oxidative stress characterized by the high circulating levels of another lipid aldehyde, malondialdehyde. In a recent Chinese study focusing on the levels of PON‐1 activity in seminal plasma, low levels of PON‐1 were associated with impaired viability and motility as well as poor sperm morphology (Gong et al ., ).…”
Section: Discussionmentioning
confidence: 99%